Exploring brand associations: an innovative methodological approach. Issue 5 (6th May 2014) - Crawford Camiciottoli, Belinda; Ranfagni, Silvia; Guercini, Simone
Abstract : Purpose: – The purpose of this exploratory study is to propose a new methodological approach to investigate brand associations. More specifically, the study aims to show how brand associations can be identified and analysed in an online community of international consumers of fashion to determine the degree of matching with company-defined brand associations. Design/methodology/approach: – The methodology is two-pronged, integrating qualitative market research techniques with quantitative text mining. It was applied to determine types and perceptions of brand associations among fashion bloggers with reference to three leading Italian fashion houses. These were then compared to brand associations found in company-generated texts to measure the degree of matching. Findings: – The results showed consistent brand associations across the three brands, as well as substantial matching with company-defined brand associations. In addition, the analysis revealed the presence of distinctive brand association themes that shed further light on how brand attributes were perceived by blog participants. Practical implications: – The methods described can be used by managers to identify and reinforce favourable brand associations among consumers. This knowledge can then be applied towards developing and implementing effective brand strategies. Originality/value: – The authors propose an interdisciplinary approach to investigate brand associations in online communities. It incorporates text mining and computer-assisted textual analysis as techniques borrowed from the field of linguistics which have thus far seen little application in marketing studies, but can nonetheless provide important insights for strategic brand management.